Is it unethical to publish data from Chinese transplant research? - Goldstein, E. (Journal of medical ethics, 2020)
Non-consensual organ procurement from prisoners in China raises serious questions regarding the ethics of Chinese transplant research. In their article, published in this issue of JME, Higgins and colleagues address these questions through the lens of publication ethics. They argue that, ‘while there are potentially compelling justifications for use [of unethical research] under some circumstances, these justifications fail when unethical practices are ongoing’.1 Consequently, they recommend non-publication of Chinese transplant research and call for a mass retraction of the articles identified in their review.2 To support their argument, Higgins and colleagues appeal to internationally recognised guidelines from the WHO3 and the World Medical Association, which assert that ‘executed prisoners must not be considered as organ and/or tissue donors’ due to the inability to acquire valid consent.4 Failing to declare an immediate publishing moratorium for transplant research involving prisoners in China, they argue, ‘undermines efforts to stop transplant-related human rights abuses, taints the evidence base, and renders those who publish and use the research complicit in the continuing harm’.5 We agree with Higgins and colleagues that non-consensual organ procurement from prisoners in China is a crime against humanity. Ongoing human rights violations in Chinese prisons are well documented and universally condemned. We also agree that the subsequent use of data acquired from unethical research is morally complex. Nonetheless, Higgins and colleagues’ arguments leave us with three …